CSF (and blood) biomarkers in cerebral amyloid angiopathy: an introduction - Jensen-Kondering, Ulf (Henry Stewart Talks, 2023)
CSF biomarkers, Amyloids in CSF and blood, Lumbar puncture, Amyloid-β 40, 42, 43 and 38, Tau proteins, Neurofilament Light Chain (NFL), Metals and blood biomarkers